Sustainable development of Chinese higher education through comparison of higher education indices - Wu, Qiong; Borhan, Mohamad Termizi (Frontiers in Education, 2024)
The purpose of this study is to undertake a comparative study of higher education indices in China and between the 31 administrative divisions of China with the international evaluation system. The analysis includes a comparison of higher education indices between China and six continents and several key countries in the world, as well as a comparison between internal regions in China and Malaysia, both of which are in Asia. The numbers and rankings of higher education institutes (HEIs) of various countries and regions listed in the QS World University Rankings (QS) over 13 years from 2010 to 2023 form the basis of corresponding higher education indices obtained through several calculation formulas. These indices are the QS Higher Education Density Index (QSHEDI), QS Higher Education Quality Index (QSHEQI), QS Higher Education Composite Index (QSHEI), and Relative QS Higher Education Composite Index (RQSHEI), and they reflect the index calculation results of the density, quality, and composite of higher education relative to the regional population. Based on the comparative analysis of the indices from multiple perspectives, this study found that there is a large gap between higher education in China and other countries, and there is also a significant imbalance in the geographical distribution of higher education resources among Chinese provinces based on the population proportion and economic impact. These disparities will hurt the sustainable development of higher education in China. Therefore, paying more attention to the international evaluation system and recognition standards like the QS Rankings becomes necessary to guide the balanced development of higher education among provinces according to the population proportion. It is also vital to improve the international influence of HEIs in China according to internationally recognized requirements so that China's higher education can develop sustainably in the process of global internationalization.